KEANEKARAGAMAN JENIS POHON PADA DUA TIPE HUTAN KAWASAN TAMAN NASIONAL LORE LINDU DI DESA BOBO SULAWESI TENGAH - Nurfiana Nurfiana; Samsulrizal.M. Sulaeman (Biology Department, Mathematics and natural science, Tadulako University, 2014)
This research was about “Tress diversity on the two different types of forest in area of Lore Lindu National Park in Bobo Village, Central Sulawesi Province”. This research was carried out on April o june 2013 in Bobo Village, area of Lore Lindu Nasional Park, Sigi District, it aimed at finding out the trees diversity of the two different types of forest in Bobo Village, area of Lore Lindu Nasional Park, Central Sulawesi province, This research was explorative Survey research used single portion method which employed purposive sampling, The result showed that on the secondary forest type was found 90 individuals out of 40 species of trees which comprised of 29 families. The species of tree which had the highest INP value was Areca Vestiaria Giseke (27,04 %) and the lowest was Polyscias nodosa (0,01 %). In the primary forest type was found 88 individuals out of 14 species of trees which comprised of 11 families. The species of tree which had the highest INP value was Syzygium Polycephaloides (56,93%) and the lowest was Oreochnide rubescens (3,29%). Diversity level of vegetation (H`) on the secondary forest type classified as the highest, whilst on the primary forest type classified as moderate (2,42 %). Index of congruence of both types of forest showed that there was a difference among communities of both forest. Keywords: Lore Lindu Nationa parkl, Bobo village, Diversity, Trees.